2003
DOI: 10.1007/s00405-002-0524-4
|View full text |Cite
|
Sign up to set email alerts
|

Betahistine dihydrochloride in the treatment of peripheral vestibular vertigo

Abstract: The present study compares the efficacy and safety of betahistine dihydrochloride to that of a placebo in recurrent vertigo resulting from Meniere's disease (MD) or in paroxysmal positional vertigo (PPV) of probable vascular origin. The design was double-blind, multicentre and parallel-group randomised. Eleven Italian cen-tres enrolled 144 patients: 75 of the patients were treated with betahistine (41 MD/34 PPV) and 69 with placebos (40 MD/29 PPV). The betahistine dosage was 16 mg twice per day for 3 months. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 15 publications
(21 reference statements)
4
66
0
4
Order By: Relevance
“…They showed that, compared to placebo, betahistine is effective in reducing the frequency, severity, and duration of vertigo and of the associated neurovegetative symptoms, as well as in improving the patients' quality of life as evaluated by questionnaires. [30][31][32][33] Only a few studies used well-controlled paradigms and measures in the laboratory to specify the role of betahistine. They reported an effect of betahistine on the vestibulo-ocular reflex for paroxysmal vertigo patients.…”
Section: Abstract: Vestibular Pathology; Vestibular Compensation; Recmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that, compared to placebo, betahistine is effective in reducing the frequency, severity, and duration of vertigo and of the associated neurovegetative symptoms, as well as in improving the patients' quality of life as evaluated by questionnaires. [30][31][32][33] Only a few studies used well-controlled paradigms and measures in the laboratory to specify the role of betahistine. They reported an effect of betahistine on the vestibulo-ocular reflex for paroxysmal vertigo patients.…”
Section: Abstract: Vestibular Pathology; Vestibular Compensation; Recmentioning
confidence: 99%
“…28 The present results are also in line with clinical studies indicating that betahistine reduced the intensity, frequency, and duration of vertigo symptoms of peripheral vestibular origin. [30][31][32][33] In patients with paroxysmal vertigo, betahistine reduced the gain of the vestibulo-ocular reflex. 34 Interestingly, these authors stressed that this drug treatment had no effect on visuo-vestibular interaction, suggesting that the site of action is in the vestibular nuclei.…”
Section: Figure 3 Effects Of Betahistine On Oculomotor Control Aftermentioning
confidence: 99%
“…Since the introduction of betahistine, it has been reported that its administration significantly reduces the incidence and severity of vertigo and produces a decrease in the incidence of nausea and emesis [1, 51, 75, 79, 81, 97, 98]. Its clinical effect has been attributed to increased blood flow in the vestibular system and cochlea [90].…”
Section: Drugs With Effects On Neurotransmitters and Neuromodulator Rmentioning
confidence: 99%
“…In a double-blind trial study, Oosterveld et al assessed the effect of betahistine on improving the vertigo in 24 patients, and showed that the severity of vertigo and also nausea and vomiting after taking betahistine has been significantly decreased [13]. Similarly, in a study conducted on 144 patients with vertigo, Simoncelli et al assessed the symptoms influence in the betahistine examined and showed that the frequency, severity and duration of attacks of vertigo in patients taking betahistine were significantly less, and also the quality of life before and after using the drug significantly improved [14]. In a randomized clinical trial, Alberta et al compared the effectiveness of betahistine with flunarizine in 52 patients with recurrent vertigo.…”
Section: Discussionmentioning
confidence: 99%